UNA REVISION TAXONOMICA DE LOS GROTEINI CHILENOS (HYMENOPTERA: ICHNEUMONIDAE) - Porter, Charils C. (Acta Entomológica Chilena, 2022)
The South American ichneumonid genera Echthropsis Brélhes and Macrogrotea Brélhes have 6 endemic species in mediterranean and valdivian Chile, whose closest relatives inhabit the Andean Puna and Cloud Foreslsof Perú. Eehthropsis (without a genal processjcontainsf. gayt (Spinola). with the ovipositor longer than the gasler, and £. curten sp. nov., whose ovipositor is half as long as the gaster. Macrogrotea is represented by Af. mperba (Schmiedeknecht), with vertical genalleelh; by Af. ebúrnea, sp. nov., with genal leeth turned mesad over the buccal cavity bul well separated; by Af. onetlh sp. nov., whose ovipositor averages 0.65 l’ore wing length and whose genal leeth are transformed into horizontal processes of which ihe trúncate ápices meet on the mid-lineof the buccal cavity; as well as by Ai. chiloe sp. nov., like Af. imetlli in its genal processes bul distinct by its ovipositor length (averages 0.80 fore wing length). The Tribe Groteini, as recognized here, ineludes the New World genera Crotea, Macrogrotea, and Eehthropsis, huí exeludes the Australian and Brasilian Labium Brullé.